The Place of The Court of First Instance in The Criminal Procedure System: Theory, Practice and Problems - С. Т. Алишаев (Scientific Trends, 2026)
This article analyzes the place and importance of the court of first instance in the criminal procedure system from scientific, theoretical and practical positions. The court of first instance is considered as the central stage of the administration of justice, at which the fate of a criminal case is decided, the criminal responsibility of a person is determined, evidence is evaluated and a court verdict is formed. The reasons for the excessive procedural workload of the trial, formalism and systemic problems arising in the activities of the court of first instance are revealed. In addition, from the point of view of increasing the efficiency of judicial activity, the need for a conceptual rethinking of the procedural role of the court of first instance is substantiated.
Keywords: Court of first instance, criminal process, trial, procedural workload, fair trial, court verdict.